PREVALENSI DAN FAKTOR RISIKO KANKER PARU-PARU DI KOTA MEDAN: STUDI KASUS KONTROL - SALOMO GARDA UTAMA SIMANJUNTAK (LP2MTBM MAKARIOZ, 2022)
The cause of the incident in Medana City is the low socialization about preventing cancer from an early age, as well as the lack of public awareness in Medan City in conducting examinations or controls on this cancer. The purpose of this study is to investigate and analyze the relationship of risk factors, in terms of age, sex, smoking habits and self-control to clinics and hospitals on the incidence of lung cancer that has infected and made the atmosphere uncomfortable in the community. This study used descriptive analytical method. The population of this study amounted to 2430 people who tested lung cancer in several sub-districts, where the samples taken amounted to 66 lung cancer patients in all hospitals in Medan City. The results of the study concluded that from several risk factors that exist and are susceptible to lung cancer, namely people in the Medan Kota District area who have smoking habits and people who lack control over the body and also disease, especially the lungs, so that lung cancer is not detected comprehensively. People who are vulnerable to the risk of lung cancer are people in Medan Kota District who are in the age range of 40-49 years and work as entrepreneurs.